2019
DOI: 10.25298/2616-5546-2019-3-1-61-65
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Action of Melatonin in Gastroesophageal Reflux Disease

Abstract: О. А. Карпович (olesjakarpovich@rambler.ru), В. И. Шишко (vshyshko@mail.ru) УО «Гродненский государственный медицинский университет», Гродно, Беларусь Введение. Известно, что степень повреждения слизистой оболочки (СО) пищевода при гастроэзофагеальной рефлюксной болезни (ГЭРБ) зависит от степени нарушения ее защитных свойств. Активно изучается роль мелатонина в обеспечении защиты СО желудочно-кишечного тракта (ЖКТ) от повреждающего действия эндогенных и экзогенных факторов. Цель исследования -изучить особеннос… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was found that OSAGS negatively affects the course of GERD, as it increases the frequency and duration of reflux from the stomach into the esophagus, aggravates damage to its mucous membrane and increases the risk of developing Barrett's esophagus [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that OSAGS negatively affects the course of GERD, as it increases the frequency and duration of reflux from the stomach into the esophagus, aggravates damage to its mucous membrane and increases the risk of developing Barrett's esophagus [5,6].…”
Section: Introductionmentioning
confidence: 99%